2020
DOI: 10.1111/are.14466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding frequency on growth performance, blood metabolites, proximate composition and digestive enzymes of Lebranche mullet ( Mugil liza ) Juveniles

Abstract: This study verified the effects of feeding frequency on growth, blood metabolites, digestive enzyme activities (alkaline protease, acid protease, amylase and lipase) and proximate composition of Lebranche mullet juveniles. Fish with initial weight of 13.6 ± 0.7 g were distributed in twelve tanks and fed one, three, five and seven times per day to apparent satiation for 60 days. While the final weight of fish fed only once a day attained just 15.4 ± 0.7 g, those fed five or seven times per day reached 54.0 ± 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Thus, stress worsened in the control group, causing more deaths. This was an unprecedented case of altered behavior in these experimental units, given that on other occasions in the same experimental units and with other marine species such as common snook Centropomus undecimalis (Michelotti et al 2020) and Lebranche mullet Mugil liza (Silva et al, 2020), this phenomenon did not occur. Another factor to be considered is that citral has sedative and anesthetic effects (Santos et al, 2022), and this may have contributed to keeping the sh in the treated groups under less stressful conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, stress worsened in the control group, causing more deaths. This was an unprecedented case of altered behavior in these experimental units, given that on other occasions in the same experimental units and with other marine species such as common snook Centropomus undecimalis (Michelotti et al 2020) and Lebranche mullet Mugil liza (Silva et al, 2020), this phenomenon did not occur. Another factor to be considered is that citral has sedative and anesthetic effects (Santos et al, 2022), and this may have contributed to keeping the sh in the treated groups under less stressful conditions.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, the amylase and pepsin activity of CI group reached a peak on the 14th day, while in CC group, the amylase and pepsin activities were lowest on the 14th day and 21st day. Similarly, it was found that the adequate interval between meals may favour feed utilization, resulting in increased activity of digestive enzymes in aquatic animals (Calixto da Silva et al, 2020; Karun Thongprajukaew et al, 2017). The higher dosage dietary nucleotide deceased the growth and digestive enzyme activities in A. leptodctylus (Safari et al, 2014), and dietary of high dose folic acid may also inhibit the amylase activities in Megalobrama amblycephala (Sesay et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding took place ve times a day until apparent satiety (Calixto et al 2020), over a period of 60 days. At the end of the experimental period, 15 sh from each treatment and control were collected for weight and total length determination.…”
Section: Experimental Design and Proceduresmentioning
confidence: 99%